2003
DOI: 10.1080/0729436032000056526
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Differences in Cheating Behaviours of IT Undergraduate and Graduate Students: The maturity and motivation factors

Abstract: Within the School of Computer Science and Software Engineering of MonashUniversity concerns have been raised about the prevalence of cheating amongst the IT students. Many isolated reports from staff of different cheating incidents collectively present a view of a problem that is widespread and multifaceted. Although indications are that these practices exist across all year levels in both undergraduate and graduate programmes, the actual extent of the problem, and whether any particular groups of students are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
1
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(66 citation statements)
references
References 7 publications
2
60
1
3
Order By: Relevance
“…While severe penalties are a deterrent, a survey of students by Sheard, Markham, and Dick (2003) found that it ranks fifth on a list of deterrents, below factors such as knowing the value of their work and pride in their work. However, simply appealing to the moral code of the students does not reduce cheating rates, while the credible threat of detection and punishment has been demonstrated to reduce the amount of cheating in a course (Hollinger & Lanza-Kaduce, 2009).…”
Section: Detection and Disciplinementioning
confidence: 99%
See 1 more Smart Citation
“…While severe penalties are a deterrent, a survey of students by Sheard, Markham, and Dick (2003) found that it ranks fifth on a list of deterrents, below factors such as knowing the value of their work and pride in their work. However, simply appealing to the moral code of the students does not reduce cheating rates, while the credible threat of detection and punishment has been demonstrated to reduce the amount of cheating in a course (Hollinger & Lanza-Kaduce, 2009).…”
Section: Detection and Disciplinementioning
confidence: 99%
“…Some students confess that they cheat because they are simply lazy (Sheard, Markham, & Dick, 2003;Wilkinson, 2009). Dennis (2004) found that a related factor, that students ran out of time because they started the assignment too late, was the top reason that students plagiarized.…”
Section: Entitlement and Apathymentioning
confidence: 99%
“…In only one question was modification required to ensure that the question was clear to respondents in both countries. Brimble and Stevenson-Clarke (2005), Marsden, Carroll and Neill (2005) and Sheard, Markham and Dick (2003) note that the majority of studies investigating ethics of students rely on survey responses that indicate attitudes and perceptions but which do not provide in-depth insights into motivations for such responses.…”
Section: Methods Of Data Gatheringmentioning
confidence: 99%
“…Reasons for not cheating were attributed to pride in one's work, a sense of moral values, and fear of penalties if caught. Studies of perceptions of plagiarism of graduate students in computing [11,13] have revealed that mature students are more committed to achieving learning outcomes and therefore less susceptible than undergraduate students, who are pressured by time and fear of failure, to adopt cheating practices.…”
Section: Related Workmentioning
confidence: 99%
“…Sheard and Dick [3,[9][10][11] conducted two surveys of undergraduate students in a School of Information Technology in 2000 and in 2010. They performed a comparative analysis of the survey data [12] of computing students' practices of cheating and plagiarism.…”
Section: Related Workmentioning
confidence: 99%